Enterprise Risk Management Adoption in Malaysia: A Disclosure Approach - Hj Togok, Salinah; Isa, Che Ruhana; Zainuddin, Suria (Asian Journal of Business and Accounting, 2016)
Manuscript type: Research paper Research aims: This paper aims to identify Malaysian companies that had adopted Enterprise Risk Management (ERM) and to determine the intensity of risk disclosure practised before and after the implementation of the 2013 Bursa Malaysia Guidelines on Risk Management and Internal Control. Design/ Methodology/ Approach: This study used a dual approach of content analysis followed by an online survey. In the first phase, content analysis was performed on the annual reports of 754 Malaysian public listed companies by using the common terms used in ERM. In the second phase, an online survey was circulated among 330 ERM adopters which were identified from the content analysis approach. Research findings: Findings from the content analysis show that the overall level of risk disclosure before and after the current guidelines had increased by five (5) per cent. Findings from the online survey further suggest that 53 per cent of respondents confirmed that ERM is indeed an integral part of their organisation. Theoretical contributions/ Originality: This study seeks to broaden current literature on risk disclosure by investigating the regulatory impact on disclosure practices. The second contribution lies in the use of dual approaches to data collection: content analysis and online survey, both of which enhance the accuracy of findings without adversely impacting on its generalisability and the costs of conducting this research. Practitioner/ Policy implications: The findings of the current study reflect on the true ERM adoption rate in this part of the region which is useful to practitioners who are still skeptical of ERM. Knowing that more than half of the public listed companies have implemented ERM may be the motivation for the non-adopters to implement ERM. Moreover, findings will encourage policy makers to introduce voluntary guidelines to regulate ERM implementation and disclosure practices in Malaysia. Research limitations/ Implications: The use of keyword search to identify ERM adopters bears the conflict of substance over form, particularly when the common terms in the disclosure do not reflect the actual practices. Future research may need to address the conflicts by using a score method that can help to improve the scientific aspects of the methodology. A framework for the analysis of risk communication and an index to measure the quality of risk disclosure can further enhance the instrument. Keywords: Annual Reports, Content Analysis, Disclosure, Keyword Search, Enterprise Risk Management JEL Classification: M41